JNK Regulation of Depression and Anxiety - Patrik Hollos; Francesca Marchisella; Eleanor T. Coffey (IOS Press, 2022)
Depression and anxiety are the most common mood disorders affecting 300 million sufferers worldwide. Maladaptive changes in the neuroendocrine stress response is cited as the most common underlying cause, though how the circuits underlying this response are controlled at the molecular level, remains largely unknown. Approximately 40% of patients do not respond to current treatments, indicating that untapped mechanisms exist. Here we review recent evidence implicating JNK in the control of anxiety and depressive-like behavior with a particular focus on its action in immature granule cells of the hippocampal neurogenic niche and the potential for therapeutic targeting for affective disorders.
Anxiety and depression are among the largest causes of disability worldwide [1]. They have complex and varied etiologies with genetic, epigenetic and environmental factors contributing to disease susceptibility. Maladaptative changes in normal stress responses leading to long lasting physical changes at the level of synapses and circuits are believed to be among the underlying causes. Antidepressant drugs have targeted the same core mechanisms for several decades, yet treatment-resistant depression is still a major problem, indicating the need for a paradigm shift [2]. Many theories of depression have been proposed, including dysregulation of monoaminergic neurotransmission, neurotrophic factors and hippocampal neurogenesis [3, 4]. However, the signalling molecules that govern mood and its underlying circuitry are largely unknown and identifying these will be essential for a comprehensive understanding of mood disorders and development of new treatments.